Intercultural Interference in the Speech Behavior of Uzbek Students Learning German - Ziyaeva , Sevara (The Lingua Spectrum, 2025)
The article presents the results of a comprehensive study of intercultural interference in the speech behavior of Uzbek students learning German. The theoretical analysis revealed significant differences between Uzbek and German linguocultures in terms of power distance, individualism/collectivism, and communication context. Empirical research involving 86 students systematized typical manifestations of interference at pragmatic, discursive, stylistic, and nonverbal levels. A correlation was established between students’ cultural attitudes and features of their speech behavior. The influence of awareness of cultural differences and intercultural communication experience on overcoming interference was revealed. Methodological recommendations were developed, including principles for creating educational materials, a system of exercises, and methods for working with authentic materials. The proposed comprehensive model for developing intercultural competence aims to overcome communication barriers and increase the effectiveness of German language teaching in the context of cultural dialogue.